Analysis of furo[3, 2‐c]tetrahydroquinoline and pyrano[3, 2‐c]tetrahydroquinoline derivatives as antitumor agents and their metabolites by liquid chromatography/electrospray ionization tandem mass spectrometry. (30th April 2013) - Hou, Xueyan; Luo, Hao; Zhong, Hao; Wu, Feng; Zhou, Meng; Zhang, Wenjuan; Han, Xuan; Yan, Guoyi; Zhang, Mengqi; Lu, Lufei; Ding, Zhenyu; He, Gu; et al.
<x xml:space="preserve">Abstract</x> RATIONALE Tetrahydroquinoline derivatives possess a broad range of biological activities. Since few studies have been reported concerning metabolites of furo[3, 2‐c]tetrahydroquinoline‐ and pyrano[3, 2‐c]tetrahydroquinoline‐derived antitumor agents, the proposed fragmentation mechanisms and their metabolites were investigated in this study. METHODS The fragmentation pathways of eight furo[3, 2‐c]tetrahydroquinoline derivatives and six pyrano[3, 2‐c]tetrahydroquinoline derivatives were analyzed using electrospray ionization tandem mass spectrometry. Hydrogen/deuterium (H/D) exchange reactions were employed to identify the proposed structures of the product ions. In addition, compounds were incubated with human liver microsomes (HLM) at 37 °C for 8 h and the related metabolites were analyzed by liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI‐MS/MS). RESULTS Two protonation modes were summarized and protonation occurring on the oxygen atom of furan or pyran ring could trigger the cleavage of the C–O bond, followed by the elimination of a molecule of water and the substituent at the C2 site, respectively. On the other hand, a proton added to the nitrogen atom may lead to the loss of dihydrofuran or dihydropyran from the protonated molecules. Apart from the general proposed fragmentation pathways above, the variations on the C2 site could result in some specific fragmentation patterns. Further incubating compound B1 with HLM in vitro produced two major metabolites, and the structures were proposed by tandem mass experiments together with the fragmentation mechanisms of these compounds. CONCLUSIONS These observations play an important role in monitoring and characterization of the presence and metabolites of furo[3, 2‐c]tetrahydroquinoline and pyrano[3, 2‐c]tetrahydroquinoline derivatives in complex mixtures, and can provide some applications in further pharmaceutical and therapeutic research. Copyright © 2013 John Wiley & Sons, Ltd.